2013
DOI: 10.1589/jpts.25.445
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Core Muscle Release Technique on Scoliosis

Abstract: Abstract.[Purpose] The object of this study was to examine the effects of the core muscle release technique (CRT) on correcting scoliosis.[Subjects] Ninety patients diagnosed with scoliosis participated in this study. [Methods] First, participants were divided into three groups according to method of treatment. The first group was administered 50 minutes of CRT five times a week for two weeks. The second group performed general exercise to treat scoliosis for the same duration. The third group received electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Finally, compression of the pelvic floor muscle was performed. One of the therapist’s hands was placed on the lower back, and the other was placed on the pubic area or above it; release was induced with light compression 14 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, compression of the pelvic floor muscle was performed. One of the therapist’s hands was placed on the lower back, and the other was placed on the pubic area or above it; release was induced with light compression 14 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Lenssinck et al 5 ) reported that exercise was the most effective conservative treatment for scoliosis, whereas Lee et al 6 ) stated that the core muscle release technique was the most effective. Schroth exercises are 3-dimensional exercises used for treating scoliosis, which were developed by Katharina Schroth in 1920 7 ) ; these provide sensorimotor and kinesthetic stimulation, thereby correcting abnormal breathing patterns present in patients with scoliosis.…”
Section: Introductionmentioning
confidence: 99%
“…Descriptive statistics were calculated for general and clinical characteristics, barriers to using research findings, research related activities, and recognition and performance of evidence-based practice. The differences in the barrier level to using research findings according to the general characteristics of the result were analyzed using the t-test, and ANOVA, and Scheffe’s test was used as a post hoc test 11 ) .…”
Section: Methodsmentioning
confidence: 99%